Measuring corporative social performance in firms: a Bayesian factor analysis approach - Agudo, José María; Gargallo, Pilar; Salvador, Manuel (Journal of Business Economics and Management, 2014)
This paper proposes a new empirical procedure for measuring Corporate Social Performance in firms, taking the Carroll model and the Stakeholder theory as theoretical supports. To that aim we use a second order factor model and we adopt a Bayesian approach that allows us to carry out a more effective statistical treatment of the missing data, using all the available information and without appealing to asymptotic results. Furthermore, we identify significant patterns of firm's behavior by means of novel statistical classification techniques and we analyze which aspects of Corporate Social Responsibility are less developed. The methodology is applied to a sample of Spanish firms. Our results show that there is a positive relationship between the firms Corporate Social Performance and their size, degree of Corporate Social Responsibility awareness and stakeholder pressure. However, Corporate Social Responsibility is not well-known in micro and small Spanish firms, which leads to a low level of implementation.